BISPHOSPHONATES IN PROPHYLAXIS OF SKELETAL-RELATED ADVERSE EVENTS IN PATIENTS WITH CASTRATION-REFRACTORY PROSTATE CANCER - E. Yu. Safronova; S. A. Sergienko; A. S. Kalpinskiy; N. V. Vorobyev; A. A. Kostin; A. D. Kaprin (Исследования и практика в медицине, 2016)
Prostate cancer (PC) is one of the most urgent problems of modern oncourology. Morbidity and mortality from this disease in theRussian Federationin recent years has been steadily increasing. Including the number of patients with metastatic and refractory to castration therapy forms of the disease is increasing. Currently, the main method of treatment of patients with metastatic prostate cancer is palliative hormone therapy (HT). Patients who have progression of tumor process, with lingering castration levels of testosterone, transferred to the stage of so-called castrate-resistant prostate cancer (CRPC). The prognosis in this group of patients is extremely unfavorable, not only because of the progression of cancer, but of complications associated primarily with the presence of bone metastases. Prevention of development of serious complications such as pathological fractures, spinal cord compression is an extremely important issue. The article presents a review of studies, the sanctifying of the problem of prevention of development of bone complications in patients with CRPC. We resent the results of large studies, including those conducted in our country demonstrated the effectiveness zoedronic acid in patients with CRPC and the presence of bone metastases.